Organizational Design, Technology and the Boundaries of the Firm - Halonen-Akatwijuka, Maija (University of Bristol, 2004)
Focus - specialization and specific technology - improves productivity but leads to more dependency and opens a door for power problems. We analyze how organizational design and the choice of technology interact with the allocation of ownership in minimizing the holdup problem. We find a novel motive for job rotation: rotation reduces holdup problems in an integrated firm. We also show that holdup problem in specific physical capital is removed in the integrated firm while holdups in specific human capital remain. Furthermore, ownership gives incentives to focus human capital on the firm.
Keywords: specialization; rotation; incomplete contracts; property rights